Predictors of Nonadherence Among Patients With Infectious Complications of Substance Use Who Are Discharged on Parenteral Antimicrobial Therapy. (13th December 2022) - Narayanan, Shivakumar; Ching, Patrick R; Traver, Edward C; George, Nivya; Amoroso, Anthony; Kottilil, Shyam
Abstract: Background: The management of invasive infections related to substance use disorder (SUD) needing parenteral antimicrobial therapy is challenging and may have poor treatment outcomes including nonadherence and lack of completion of parenteral antimicrobial therapy. Methods: In this retrospective cohort of 201 patients with invasive infections related to SUD, we looked at frequency and determinants of unfavorable outcomes including nonadherence. Results: Seventy-nine percent of patients with SUD-related infection completed parenteral antibiotic therapy in skilled nursing facilities. A total of 21.5% of patient episodes had documentation of nonadherence. Nonadherence was higher in patients with active injection drug use (IDU) (28.5% versus 15% in non IDU; adjusted odds ratio [OR] 2.36; 95% confidence interval [CI], 1.1–5.5; P = .024), patients with active SUD in the prior year (24.5% vs 11%, P = .047), patients with use of more than 1 illicit substance (30.3% vs 17%, P = .031), as well as in people experiencing homelessness (32.8% vs 15.7% in stably housed, P = .005). In a multivariate model, nonadherence was significantly associated with IDU (OR, 2.38; 95% CI, 1.03–5.5) and homelessness (OR, 2.25; 95% CI, 1.01–4.8) Medication for opioid use disorder was prescribed at discharge in 68% of overall cohort and was not associated with improved outcomes for any of the above groups. Conclusions: Nonadherence to parenteral antimicrobial therapy is high in the most vulnerable patients with unstable high-risk SUD and adverse social determinants of health. Abstract : In patients hospitalized with SUD-related infections, completion of postdischarge parenteral antibiotic therapy may be suboptimal, and nonadherence is associated with those with high risk, unstable substance use, active use, or use of multiple substances, and among people experiencing homelessness.